Copper-catalyzed intramolecular dehydrogenative cyclization: direct access to sensitive formyl-substituted imidazo[1, 2-a]pyridines. Issue 113 (2nd November 2015) - Zhai, Li-Hai; Guo, Li-Hong; Sun, Bai-Wang
Abstract : A direct method for the synthesis of formyl-substituted imidazo[1, 2- a ]pyridines was achieved easily from cyclization of aminopyridines and cinnamaldehydes via copper catalysis. Abstract : A direct method for the synthesis of formyl-substituted imidazo[1, 2- a ]pyridines was achieved easily from cyclization of aminopyridines and cinnamaldehydes via copper catalysis. This oxidative cyclization process involved direct C–H bond functionalization, and C–C/C–N bond formation. In this transformation, the sensitive aldehyde group was preserved under oxidative conditions.